Information Identification Skills and Research Output of Academic Librarians in Universities in South-South Geopolitical Zone of Nigeria - Ilevbare, Godson Ehimiyein; Enang, Uduak U. (Ghana Library Journal, 2022)
This study investigated the relationship between information identification skills and the research output of academic librarians in universities in the South-South Geopolitical Zone of Nigeria with a corresponding specific objective, research question, and research hypothesis. To effectively drive the study two theories were adopted. The theory of social-cultural learning for the independent variable (information identification skills), and the theory of self-efficacy for the dependent variable (research output of academic librarians). More so, a conceptual review of literature on information identification skills and research output was carried out and a specific empirical review of the literature with extrinsic similarity and dissimilarity to the study was also done. The study adopted the correlational research design as the research design while the study area was the South-South Geopolitical Zone of Nigeria. The population of the study comprised 252 academic librarians from 14 libraries and faculties. The census technique was used to select the research participants 252. The researcher-developed questionnaire entitled: “Information Identification Skills and the Research Output of Academic Librarians Questionnaire (IISROALQ)” was used to collect data while the reliability test results using the Cronbach Alpha formula in SPSS showed an average coefficient of .83 which signified that the instrument was reliable for the study. Data was collected from the various universities by the researchers and their trained assistants by following the requisite ethical procedures. The data collected was analysed using frequencies and percentages for the research question, while the test of hypothesis at ≤ 0.05 level of significance was carried out with the Chi-Square Test of Independence. The result showed that information identification skills have a positive significant relationship with the research output of academic librarians with p-value = 0.00, and Phi coefficient of 2.49 indicating a very large extent of a positive relationship. In conclusion, it was recommended that the National University commission should make proficient utilization of information literacy skills by academic librarians as part of the requirement to assess their suitability for performance within the scholarly communities. Also, the university management should give attention to constant information literacy skills programs to enhance the literacy skills of the academic staff to be able to produce quality and rich research output.